Calidad de sueño como predictor de depresión, ansiedad y estrés en socios de “En las huellas del banco Grameen”, Loja - Pineda Calva, Leslye Pauleth (2023)
Sleep is associated with important physiological processes, however, the trend towards sleep deprivation is gradually increasing, causing a decrease in the quality of sleep, and a greater predisposition to physical and mental alterations. The purpose of this research was to evaluate the sleep quality index, identify the degree of depression, anxiety and stress and analyze its relationship in members of the corporation "In the footsteps of the Grameen bank", savings and credit cooperative, Loja. With a quantitative, cross-sectional approach and a sample of 277 partners, in whom the Pittsburgh Sleep Quality Index (PSQI) and the Depression, Anxiety and Stress scale (DASS-21) were applied, it was obtained that 45.5% (n= 126) were good sleepers and 54.5% (n= 151) poor sleepers, with a predominance of the female sex, who were the majority, in the sample of this research. 15.2% (n=42) presented mild depression; 12.3% (n=34) moderate; 6.1% (n=17) extremely severe and 4.3% (n=12) severe. On the other hand, 16.6% (n=46) expressed moderate anxiety; 13% (n=36) mild; 11.6% (n=32) extremely severe and 6.5% (n=18) severe. Likewise, 12.6% (n=35) revealed mild stress; 10.8% (n=30) moderate; 10.5% (n=29) severe and 6.5% (n=18) extremely severe. Most affected age groups were mature adults, females and young adults, males. When relating the variables, a statistically significant association was found, with a p value of 0.0001. Concluding that there is an inverse relationship, that is, the worse the quality of sleep, the greater the predisposition to suffer from these psychological disorders